Knowledge and interest of north-central Romanian mothers regarding children oral health prevention - A questionnaire based study - Tohati Adrian; Bechir Farah ("George Emil Palade" University of Medicine, Pharmacy, Science, and Technology of Targu Mures, 2019)
Introduction: The development and eruption of teeth should be followed by the dentist, which is why periodic check ups are required.